Solid-state electrolyte composite film, preparation method thereof, all-solid-state battery, and battery pack

CN122992155APending Publication Date: 2026-10-27ZHONGTIAN ENERGY STORAGE TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611461824.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

硫化物固态电解质(如Li2S-P2S5)因离子电导率高(接近液态电解液水平)和可加工性优异而备受关注,但其存在空气稳定性差(易水解)、成本高(前驱体硫化锂价格昂贵)以及与活性材料界面接触差等问题,需在高压(>20MPa)条件下运行,限制了其规模化应用

Benefits of technology

[0052]本申请实施例提供的固态电解质复合薄膜及其制备方法、全固态电池、电池组,通过采用第一PVDF膜层和第二PVDF膜层上下包覆含有β相PVDF的极化PVDF膜层,既能改善固态电解质与电极活性层的界面接触,降低界面阻抗,提升锂离子传输效率;其中的极化PVDF膜层也能通过机械性能和连续离子通道,有效抑制锂枝晶生长,提高所得固态电池复合薄膜的离子电导率和循环寿命。该固态电解质复合额薄膜制备得到的全固态电池盒的能量密度能够得到显著提升,适配eVTOL等高能量密度需求场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992155A_ABST
    Figure CN122992155A_ABST
Patent Text Reader

Abstract

The embodiment of the application provides a solid-state electrolyte composite film, a preparation method thereof, a full solid-state battery and a battery pack. The solid-state electrolyte composite film comprises a polarized PVDF film layer and first and second PVDF film layers arranged on two sides of the polarized PVDF film layer respectively; the polarized PVDF film layer comprises a first crystalline phase, and the first crystalline phase comprises first beta-phase PVDF. The solid-state electrolyte composite film achieves the effects of interface optimization, dendrite inhibition and ultrathinning through a three-layer composite structure, thereby improving the effects of ion conductivity and cycle life of the solid-state electrolyte composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of batteries, and in particular to a solid electrolyte composite film and its preparation method, an all-solid-state battery, and a battery pack. Background Technology

[0002] Solid-state batteries, as a core technology for next-generation high-safety, high-energy-density energy storage systems, are widely used in new energy vehicles, consumer electronics, energy storage systems, and emerging fields such as eVTOL (eVTOL) and humanoid robots. By replacing liquid electrolytes with solid electrolytes, solid-state batteries avoid the leakage problems associated with liquid electrolytes. Furthermore, their structural design is more flexible, allowing them to be adapted to high-energy-density positive and negative electrode materials (such as high-nickel ternary cathodes and lithium metal anodes). They also possess intrinsic safety advantages, potentially eliminating the risk of thermal runaway.

[0003] Current all-solid-state battery technologies are mainly based on solid electrolyte systems such as sulfides, oxides, polymers, and halides. Sulfide solid electrolytes (such as Li₂S-P₂S₅) have attracted much attention due to their high ionic conductivity (approaching that of liquid electrolytes) and excellent processability. However, they suffer from poor air stability (prone to hydrolysis), high cost (the precursor lithium sulfide is expensive), and poor interfacial contact with active materials. They also require operation under high pressure (>20 MPa), limiting their large-scale application. Furthermore, the weak mechanical properties of sulfide electrolyte films make it difficult to further reduce their thickness (typically 20-40 μm), thus affecting battery energy density. Oxide solid electrolytes (such as LLZO) have high ionic conductivity and good thermal stability, but they are brittle, difficult to form ultrathin films, and have poor interfacial compatibility with electrode materials, resulting in high interfacial impedance. Polymer solid electrolytes (such as PEO-LiTFSI) exhibit excellent flexibility and processability, and good interfacial contact with active materials; however, their room-temperature ionic conductivity is relatively low (<1.0 × 10⁻⁶). -4 S·cm -1 This requires high-temperature operation (above 60°C), making it difficult to meet the needs of room-temperature applications. Halogen solid electrolytes (such as Li3InCl6) have attracted attention in recent years due to their high ionic conductivity and wide electrochemical window, but their synthesis process is complex and costly, and the interfacial stability with the lithium metal anode still needs to be verified.

[0004] It is evident that the industrialization of all-solid-state batteries still faces challenges such as high interfacial impedance between solid electrolyte and electrode materials, insufficient ionic conductivity, risk of lithium dendrite penetration, and limitations on energy density due to electrolyte film thickness. There is an urgent need to design an ultra-thin solid electrolyte film that can achieve high ionic conductivity at room temperature and pressure, while also enabling all-solid-state batteries to have a long cycle life and high energy density. Summary of the Invention

[0005] This application provides a solid electrolyte composite film and its preparation method, an all-solid-state battery, and a battery pack, which can improve the energy density, rate performance, and cycle life of the all-solid-state battery.

[0006] In a first aspect, embodiments of this application provide a solid electrolyte composite film comprising a first PVDF film layer, a polarized PVDF film layer, and a second PVDF film layer stacked sequentially; the polarized PVDF film layer includes a first crystalline phase, the first crystalline phase including a first β-phase PVDF.

[0007] In one possible implementation, the mass percentage of the first β-phase PVDF in the first crystalline phase is 30%-90%.

[0008] In one possible implementation, the first PVDF film layer includes a second crystalline phase, the second crystalline phase including a second β-phase PVDF;

[0009] The mass percentage of the second β-phase PVDF in the second crystalline phase is 24%-28%;

[0010] And / or, the second PVDF film layer includes a third crystalline phase, the third crystalline phase including a third β-phase PVDF;

[0011] The mass percentage of the third β-phase PVDF in the third crystalline phase is 24%-28%.

[0012] In one possible implementation, the first PVDF film layer includes a first PVDF, a first solid electrolyte, and a first lithium salt;

[0013] And / or, the second PVDF membrane layer includes a second PVDF, a second solid electrolyte, and a second lithium salt.

[0014] In one possible implementation, the mass ratio of the first PVDF to the first solid electrolyte in the first PVDF film layer is 1:(0.1-1).

[0015] And / or, in the second PVDF film layer, the mass ratio of the second PVDF to the second solid electrolyte is 1:(0.1-0.6).

[0016] And / or, the mass fraction of the first lithium salt in the first PVDF film is 1%-10%;

[0017] And / or, the mass fraction of the second lithium salt in the second PVDF film is 1%-10%.

[0018] In one possible implementation, the first solid electrolyte comprises one of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium sulfur phosphorus chlorine, lithium sulfur phosphorus germanium, polyethylene glycol dimethacrylate, and polyethylene terephthalate acrylate.

[0019] And / or, the second solid electrolyte comprises one of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium sulfur phosphorus chloride, lithium sulfur phosphorus germanium, polyethylene glycol dimethacrylate, and polyethylene terephthalate acrylate.

[0020] And / or, the first lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide;

[0021] And / or, the second lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

[0022] Secondly, this application provides a method for preparing the above-mentioned solid electrolyte composite film, comprising: preparing a third slurry containing a third PVDF, a third solid electrolyte and a third lithium salt into a third PVDF film layer, and then stretching the third PVDF film layer to obtain a polarized PVDF film layer;

[0023] A first PVDF, a first solid electrolyte, and a first lithium salt are dissolved in a first solvent to form a first slurry. The first slurry is then used to form a first PVDF film layer on one side surface of the polarized PVDF film layer by a first electrospinning method, thereby obtaining a solid electrolyte bilayer film.

[0024] The second PVDF, the second solid electrolyte, and the second lithium salt are dissolved in a second solvent to form a second slurry; the second slurry is then used to form a second PVDF film layer on the other surface of the polarized PVDF film layer in the solid electrolyte bilayer film by a second electrospinning method, thus obtaining a solid electrolyte composite film precursor.

[0025] The solid electrolyte composite film precursor is heat-treated to obtain the solid electrolyte composite film.

[0026] In one possible implementation, the third PVDF in the third slurry has a mass fraction of 5% to 27.5%.

[0027] And / or, the third lithium salt has a mass fraction of 1%-10% in the third slurry;

[0028] And / or, the stretching ratio is (1.1-1.5):1;

[0029] And / or, the stretching rate is 1 mm / min to 5 mm / min.

[0030] In one possible implementation, the solid content of the first slurry is 10%-30%;

[0031] And / or, the mass fraction of the first PVDF in the first slurry is 20wt%-30wt%;

[0032] And / or, the mass fraction of the first solid electrolyte in the first slurry is 2wt%-5wt%;

[0033] And / or, the mass fraction of the first lithium salt in the first slurry is 1wt%-10wt%;

[0034] And / or, the solid content of the second slurry is 10%-30%;

[0035] And / or, the mass fraction of the second PVDF in the second slurry is 20wt%-30wt%;

[0036] And / or, the mass fraction of the second solid electrolyte in the second slurry is 2wt%-5wt%;

[0037] And / or, the mass fraction of the second lithium salt in the second slurry is 1wt%-10wt%.

[0038] In one possible implementation, in the first electrospinning method, the supply rate of the first slurry is 0.5 ml / h-5 ml / h;

[0039] And / or, the polarized PVDF film layer is attached to the first roller, the rotation speed of the first roller is 100 rpm to 1500 rpm;

[0040] And / or, the spinning distance of the first electrospinning method is 10cm-20cm;

[0041] And / or, the spinning pressure of the first electrospinning method is 10kV-20kV;

[0042] And / or, the spinning temperature of the first electrospinning method is 25℃-40℃.

[0043] In one possible implementation, in the second electrospinning method, the supply rate of the second slurry is 0.5 ml / h-5 ml / h;

[0044] And / or, the solid electrolyte bilayer film is attached to the second roller, the second roller rotating at a speed of 100 rpm to 1500 rpm;

[0045] And / or, the spinning distance of the second electrospinning method is 10cm-20cm;

[0046] And / or, the spinning pressure of the second electrospinning method is 10kV-20kV;

[0047] And / or, the spinning temperature of the second electrospinning method is 25℃-40℃.

[0048] In one possible implementation, the heat treatment temperature is 110°C-150°C;

[0049] The heat treatment time is 0.5 min to 5 min.

[0050] Thirdly, embodiments of this application provide an all-solid-state battery, including a positive electrode, a negative electrode, and the above-described solid electrolyte composite film or a solid electrolyte composite film prepared by the above-described preparation method.

[0051] Fourthly, embodiments of this application provide a battery pack including the aforementioned all-solid-state battery.

[0052] The solid electrolyte composite film, its preparation method, all-solid-state battery, and battery pack provided in this application embodiment utilize a polarized PVDF film layer containing β-phase PVDF, which is wrapped top and bottom with a first PVDF film layer and a second PVDF film layer. This improves the interfacial contact between the solid electrolyte and the electrode active layer, reduces interfacial impedance, and enhances lithium-ion transport efficiency. Furthermore, the polarized PVDF film layer effectively suppresses lithium dendrite growth through its mechanical properties and continuous ion channels, thereby improving the ionic conductivity and cycle life of the resulting solid-state battery composite film. The energy density of the all-solid-state battery pack prepared using this solid electrolyte composite film is significantly improved, making it suitable for high-energy-density applications such as eVTOL. Attached Figure Description

[0053] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0054] Figure 1 This is a schematic diagram of the structure of the solid electrolyte thin film provided in this application;

[0055] Figure 2 This is a side view of the solid electrolyte film provided in this application.

[0056] Figure label:

[0057] 001: Polarized PVDF film layer; 002: First PVDF film layer; 003: Second PVDF film layer;

[0058] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0059] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numbers in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this application as detailed in the appended claims.

[0060] First, let me explain the terms used in this application:

[0061] α-phase PVDF: refers to the crystal structure of PVDF molecular chains exhibiting the TGTG' (trans-trans-trans) conformation; this conformation causes fluorine and hydrogen atoms on the chain to be arranged alternately in space, resulting in the cancellation of dipole moments and the overall nonpolarity.

[0062] β-phase PVDF: refers to the crystal structure of PVDF molecular chains exhibiting an all-trans (TTTT) conformation; this highly extended serrated conformation places all fluorine atoms on one side of the chain and all hydrogen atoms on the other side, forming a strong net dipole moment and exhibiting strong polarity overall.

[0063] In existing all-solid-state batteries, while sulfide electrolytes possess high ionic conductivity, they are prone to side reactions upon contact with lithium metal anodes, leading to SEI layer thickening and increased interfacial impedance. Furthermore, the porosity between particles after roll forming cannot effectively prevent lithium dendrite growth, posing a short-circuit risk. Polymer electrolytes, while exhibiting good interfacial compatibility, suffer from low conductivity at room temperature, requiring high-temperature operation and limiting their use in room-temperature applications. Moreover, electrolyte film thickness is negatively correlated with energy density, and current technologies struggle to reduce electrolyte film thickness below 12 μm. In high-energy-density applications such as eVTOL, these issues directly result in large battery size and weight, limiting aircraft range; in energy storage systems, interfacial impedance and cycle life issues affect long-term battery reliability.

[0064] The solid electrolyte composite film provided in this application solves the core problems in the prior art, such as poor interface contact between solid electrolyte and electrode material, risk of lithium dendrite penetration, and contradiction between electrolyte film thickness and energy density, by using a first PVDF film layer and a second PVDF film layer to coat polarized PVDF film layers on the top and bottom.

[0065] The technical solution of this application and how the technical solution of this application solves the above-mentioned technical problems are described in detail below with specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments. The embodiments of this application will now be described with reference to the accompanying drawings.

[0066] Figure 1 This is a schematic diagram of the structure of the solid electrolyte composite film provided in this application. Figure 2 This is a side view of the solid electrolyte composite film provided in this application. Figure 1 or Figure 2 As shown, the solid electrolyte composite film includes: a first PVDF film layer 002, a polarized PVDF film layer 001, and a second PVDF film layer 003 stacked sequentially; the polarized PVDF film layer 001 includes a first crystalline phase, which includes a first β-phase PVDF.

[0067] It is understandable that β-phase PVDF has the highest polarity among all PVDF crystal phases, with all its fluorine (F) and hydrogen (H) atoms arranged on both sides of the molecular chain, forming a strong and well-ordered dipole moment. This strong polarity makes its affinity for polymer electrolytes, which also have polarity, much higher than that of the non-polar α-phase, effectively reducing interfacial energy and promoting excellent interfacial contact between the electrolyte and the electrode material (especially the positive electrode) surface.

[0068] The first β-phase PVDF exhibits a dendritic dispersion within the polarized PVDF film. This dendritic crystal structure not only forms continuous ion transport channels at the microscale, providing a low-impedance migration path for lithium ions, but its large specific surface area also exposes more β-PVDF polar interfaces. The strongly negatively charged fluorine atoms and positively charged hydrogen atoms at these interfaces can weakly interact with the anions and lithium ions in lithium salts (such as LiPF6). In particular, it can dissociate lithium salts to a certain extent and weaken the lithium-ion exchange through dipole-ion interactions. 0 The Coulomb force between lithium ions and anions increases the concentration of free lithium ions, which in turn increases the effective migration path of lithium ions, lowers the migration energy barrier, and enhances the transport directionality, resulting in higher ionic conductivity and ion transference number.

[0069] Furthermore, the strong polarity and dipole field provided by the first β-phase PVDF can also target anions with larger volume and lower charge density (such as TFSI). - This creates a stronger binding effect, relatively increasing the lithium-ion transference number. A high transference number reduces anion accumulation at the interface, thereby homogenizing the lithium-ion concentration distribution on the surface of the negative electrode (especially the lithium metal negative electrode) and preventing localized Li-ion buildup. +"Cutting-edge growth" is driven by scarcity. It is evident that the electric dipole moment of the polarized PVDF film helps to homogenize the electric field distribution on the lithium anode surface at the microscopic level, guiding uniform Li⁺ deposition, thereby reducing concentration polarization during charging and discharging, and improving the rate performance and cycle life of the battery.

[0070] During battery cycling, when lithium ions are deposited on the negative electrode side, the mechanical properties of the first β-phase PVDF can effectively suppress the disordered growth of lithium dendrites, preventing dendrites from piercing the electrolyte membrane. Furthermore, the dendritic crystal structure can disperse the deposition stress of lithium ions, reduce the non-uniformity of local current density, thereby reducing the likelihood of dendrite formation, significantly improving the interface stability on the negative electrode side, reducing the risk of battery short circuits, and extending the battery's cycle life and high-temperature performance.

[0071] The first and second PVDF film layers on both sides can provide good mechanical support for the solid electrolyte particles contained in the solid electrolyte composite film and their compatibility with the electrode. The polarized PVDF film layer in the middle, as a "functional layer", also has high elastic modulus and mechanical strength, which can optimize the interfacial contact between the solid electrolyte and the electrode.

[0072] The good interfacial contact provided by the three-layer PVDF film and the stable PVDF material itself (with a wide electrochemical window of about 4.5V vs. Li⁺ / Li) not only help stabilize the interface of high-voltage cathodes (such as NCM811 and lithium-rich manganese-based materials), indirectly allowing the use of cathode materials with higher energy density, but also enable better interfacial contact and more uniform deposition between the solid electrolyte and the anode (lithium metal), which helps to form a more stable and uniform SEI film and suppress heterogeneous dendrite nucleation from the source.

[0073] The three-layer composite structure of solid electrolyte composite films, with its excellent mechanical strength and interfacial stability, can achieve overall film thinning while ensuring safety, thereby increasing the space for active materials to fill inside the all-solid-state battery and improving the volumetric energy density of the all-solid-state battery.

[0074] In some specific embodiments, the mass percentage of the first β-phase PVDF in the first crystalline phase is 30%-90%.

[0075] In this embodiment, by controlling the mass ratio of the first β-phase PVDF in the polarized PVDF film layer to 30%-90%, it is helpful to construct a dense and continuous ion transport channel in the polarized PVDF film layer. This ordered structure can guide lithium ions to achieve uniform deposition on the electrode surface, effectively suppress the growth of lithium dendrites, and avoid battery short circuits caused by dendrites piercing the separator. In the solid electrolyte composite film provided in this application, the polarized PVDF layer with high β-phase content in the middle layer can also provide a high dielectric environment, optimize the lithium ion solvation structure through this layer, and allow it to enter the electrodes on both sides in a more stable state, thereby reducing the interfacial side reactions with the positive and negative electrodes, helping to maintain the long-term stability of the electrode / electrolyte interface, and preventing battery performance degradation caused by the accumulation of interfacial side reaction products.

[0076] For example, the mass percentage of the first β-phase PVDF in the first crystalline phase of the polarized PVDF film can be 30%, 35%, 40%, 45%, 50%, 54.9%, 55%, 60%, 65%, 70%, 75%, 77.8%, 80%, 81.5%, 85%, 88.9%, 90%, or any combination thereof.

[0077] In some specific embodiments, the first PVDF film layer includes a second crystallinity, and the second crystalline phase includes a second β-phase PVDF; the mass percentage of the second β-phase PVDF in the second crystalline phase is 24%-28%.

[0078] In some specific embodiments, the second PVDF film layer includes a third crystalline phase, which includes a third β-phase PVDF; the mass percentage of the third β-phase PVDF in the third crystalline phase is 24%-28%.

[0079] By controlling the mass percentage of the second β-phase PVDF in the first PVDF film to the second crystalline phase, or the mass percentage of the third β-phase PVDF in the second PVDF film to the third crystalline phase, between 24% and 28%, appropriate amorphous regions and a small amount of α-phase PVDF can be retained to provide flexibility. This allows the first and second PVDF films to buffer stress with slight deformation during thermal expansion and contraction and changes in electrode volume. Furthermore, the β-phase PVDF within this mass percentage range can form a continuous crystalline network, stabilizing the overall film structure and preventing delamination and pore expansion during long-term cycling. Simultaneously, the polar framework formed by the β-phase PVDF in the first and second PVDF films restricts anion movement, allowing only Li+ directional conduction, which helps alleviate anion accumulation at high rates, reduces concentration polarization, and slows down capacity decay under high current.

[0080] For example, the mass percentage of the second β-phase PVDF in the second crystalline phase can be a range of 24%, 25%, 26%, 27%, 28%, or any two of these.

[0081] For example, the mass percentage of the third β-phase PVDF in the third crystalline phase can be a range of 24%, 25%, 26%, 27%, 28%, or any two of these.

[0082] In some specific embodiments, the first PVDF film layer includes a first PVDF, a first solid electrolyte, and a first lithium salt.

[0083] In some specific embodiments, the second PVDF film layer includes a second PVDF, a second solid electrolyte, and a second lithium salt.

[0084] In this embodiment, the first or second solid electrolyte added to the first PVDF film layer and / or the second PVDF film layer is itself a superionic conductor. When its addition amount reaches the percolation threshold, these particles will come into contact with each other, forming a continuous, ultra-high-speed lithium-ion transport network that runs through the entire film layer, greatly improving ionic conductivity and transport number. The ultra-high ionic conductivity makes the lithium-ion flow extremely uniformly distributed on the negative electrode surface, fundamentally avoiding dendrite nucleation caused by local aggregation.

[0085] In addition, high-modulus sulfide particles can be embedded in PVDF polymer as "hard points", which can not only improve the elastic modulus, tensile strength and puncture strength of the composite film, making it more difficult for lithium dendrites to puncture it, but also reduce the thermal shrinkage and swelling of PVDF polymer at high temperature, thereby improving the thermal stability and structural integrity of solid electrolyte composite film.

[0086] In some specific embodiments, the mass ratio of the first PVDF to the first solid electrolyte in the first PVDF membrane layer is 1:(0.1-1).

[0087] In this embodiment, by controlling the mass ratio of the first PVDF to the first solid electrolyte to be 1:(0.1-1), it is beneficial to balance the mechanical properties of the first PVDF film while controlling the continuity of the three-dimensional ion transport network composed of the first solid electrolyte in the first PVDF film, maintaining the overall toughness, flexibility and soft contact capability with the electrode of the solid electrolyte composite film, suppressing the formation of lithium dendrites, thereby obtaining better interface contact effect and optimizing the electrochemical stability and safety of the obtained all-solid-state battery.

[0088] For example, the mass ratio of the first PVDF to the first solid electrolyte can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1 or any combination thereof.

[0089] In some specific embodiments, the mass ratio of the second PVDF to the second solid electrolyte in the second PVDF membrane layer is 1:(0.1-0.6).

[0090] As explained above regarding the reasons for controlling the mass ratio of the first solid electrolyte to the first PVDF in the first PVDF film layer, in the second PVDF film layer, by controlling the mass ratio of the second PVDF to the second solid electrolyte to be 1:(1-0.6), a more continuous sulfide phase and polymer phase can be obtained, thereby providing higher ionic conductivity, flexibility, film-forming properties, and interfacial contact, ensuring efficient ion transfer between the organic and inorganic phases, and reducing impedance.

[0091] For example, the mass ratio of the second PVDF to the second solid electrolyte can be a range of 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6 or any two of these.

[0092] In some specific embodiments, the mass fraction of the first lithium salt in the first PVDF film layer is 1% to 10%.

[0093] In some specific embodiments, the mass fraction of the second lithium salt in the second PVDF film layer is 1% to 10%.

[0094] By controlling the mass fraction of the first or second lithium salt contained in the first PVDF film layer and / or the second PVDF film layer to 1%-10%, on the one hand, it can promote the full dissociation of lithium salt, providing the battery with sufficient free-moving lithium ions, which is conducive to achieving high ionic conductivity; on the other hand, this content of lithium salt also helps to form a thin and chemically stable solid electrolyte interface film during cycling, effectively preventing side reactions and facilitating intestinal cycle life; furthermore, the corresponding polymer matrix can maintain the integrity of the PVDF film layer, giving it the necessary compressive modulus to resist and inhibit the growth and penetration of lithium dendrites, ensuring that the battery can cycle safely and for a long time.

[0095] For example, the mass fraction of the first lithium salt in the first PVDF film layer can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination thereof; the mass fraction of the second lithium salt in the second PVDF film layer can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination thereof.

[0096] It should be noted that the mass fraction of the first lithium salt in the first PVDF film layer may be the same as or different from the mass fraction of the second lithium salt in the second PVDF film layer.

[0097] In some specific embodiments, the first solid electrolyte includes one of lithium titanium aluminum phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), lithium sulfur phosphorus chloride (LPSCI), lithium sulfur phosphorus germanium (LGPS), lithium lanthanum niobium oxyfluorine (LLNOF), polyethylene glycol dimethacrylate (PEGDMA), and polyethylene terephthalate acrylate (PETEA).

[0098] In some specific embodiments, the second solid electrolyte includes one of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), lithium sulfur phosphorus chloride (LPSCI), lithium sulfur phosphorus germanium (LGPS), lithium lanthanum niobium oxyfluorine (LLNOF), polyethylene glycol dimethacrylate (PEGDMA), and polyethylene terephthalate acrylate (PETEA).

[0099] In some specific embodiments, the first lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI);

[0100] In some specific embodiments, the second lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0101] In some specific embodiments, the first PVDF film layer includes a second crystalline phase, the second crystalline phase includes a second β-phase PVDF, and the mass percentage of the second β-phase PVDF in the second crystalline phase is 24%-88%.

[0102] In some specific embodiments, the second PVDF film layer includes a third crystalline phase, which includes a third β-phase PVDF, and the mass percentage of the third β-phase PVDF in the third crystalline phase is 24%-88%.

[0103] Since the first PVDF film layer and / or the second PVDF film layer contain solid electrolyte and lithium salt, the mass fraction of the second β-phase PVDF and the third β-phase PVDF contained therein in the crystalline phase is controlled to be 24%-88%, which is beneficial to improve the interfacial wettability inside the solid electrolyte composite film, making it less likely for voids to appear between layers and reducing interfacial contact resistance; at the same time, it can also adsorb and guide the migration of lithium ions, reduce the interfacial impedance between layers, improve the overall room temperature ion conductivity of the solid electrolyte composite film; and block the side reactions on the electrode side, inhibit lithium salt decomposition, reduce the probability of lithium crystallization, and improve the stability of the battery.

[0104] For example, the mass percentage of the second β-phase PVDF in the second crystalline phase can be a range of 24%, 30%, 40%, 50%, 60%, 70%, 72.8%, 73.5%, 76.5%, 80%, 81.9%, 82.7%, 86.3%, 90%, or any combination thereof.

[0105] For example, the mass percentage of the third β-phase PVDF in the third crystalline phase can be 24%, 30%, 40%, 50%, 60%, 70%, 72.8%, 73.5%, 76.5%, 79.3%, 80%, 81.9%, 82.7%, 86.3%, 90%, or any combination thereof.

[0106] In some specific implementations, the thickness of the solid electrolyte is 10µm to 20µm.

[0107] The solid electrolyte composite film provided in this application significantly improves the interfacial contact between the solid electrolyte composite film and the electrode, reduces interfacial impedance, and enhances lithium-ion transport efficiency by setting a polarized PVDF film layer containing β-phase PVDF between the first and second PVDF film layers. Simultaneously, the polarized PVDF film layer, through enhanced mechanical properties and the design of continuous ion channels, effectively suppresses lithium dendrite growth and improves battery safety; the three-layer composite structure design significantly improves the battery's volumetric energy density. In summary, the obtained solid electrolyte composite film significantly improves the battery's cycle stability and coulombic efficiency.

[0108] This application also provides a method for preparing the above-mentioned solid electrolyte composite film, including:

[0109] A third slurry containing a third PVDF, a third solid electrolyte, and a third lithium salt is used to prepare a third PVDF film layer. Then, the third PVDF film layer is stretched to obtain a polarized PVDF film layer.

[0110] The first PVDF, the first solid electrolyte and the first lithium salt are dissolved in the first solvent to form a first slurry. The first slurry is then used to form a first PVDF film layer on one side of the polarized PVDF film layer by a first electrospinning method to obtain a solid electrolyte bilayer film.

[0111] The second PVDF, the second solid electrolyte, and the second lithium salt are dissolved in the second solvent to form a second slurry; the second slurry is then used to form a second PVDF film layer on the other surface of the polarized PVDF film layer in the solid electrolyte bilayer film by a second electrospinning method, thus obtaining a solid electrolyte composite film precursor.

[0112] The solid electrolyte composite film precursor is heat-treated to obtain the solid electrolyte composite film.

[0113] Specifically, in preparing the polarized PVDF film, the third PVDF, the third solid electrolyte, and the third lithium salt are first dissolved in a third solvent (such as NMP) to form a third slurry. Then, the third slurry is cast using a solution casting method, and the cast slurry is dried to obtain the polarized PVDF film precursor. The polarized PVDF film precursor is then stretched. Under tensile stress, the α-phase (non-polar, TGTG' conformation) of PVDF is straightened and rearranged, partially transforming into the all-trans conformation (TTTT) β-phase, resulting in a polarized PVDF film mainly composed of β-phase PVDF.

[0114] In some specific implementations, the mass fraction of the third PVDF in the third slurry is 5%-27.5%.

[0115] By controlling the mass fraction of the third PVDF in the third slurry to be 5%-27.5%, the polymer chains of the third PVDF exhibit good dispersibility and appropriate entanglement in the third solvent. During subsequent solvent evaporation and drying (often accompanied by thermal annealing), this facilitates the ordered rearrangement of the polymer chains under external fields (such as subsequent stretching or electric field polarization), thereby inducing the formation of β-phase crystals. It also allows the polymer chains of the third PVDF to fully intertwine and accumulate during the evaporation of the third solvent, forming a dense, uniform, and defect-free continuous film. Furthermore, the mass fraction of the third PVDF determines the "skeleton" density of the polymer matrix in the first PVDF film. Within this mass fraction range, it ensures that the first PVDF film has sufficient mechanical strength to suppress dendrite penetration while maintaining good flexibility to adapt to volume changes during battery cycling.

[0116] For example, the mass fraction of the third PVDF in the third slurry can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 27.5%, or any combination thereof.

[0117] In some specific embodiments, the mass fraction of the third lithium salt in the third slurry is 1%-10%.

[0118] It is understandable that the ionic conductivity (σ) of the film is determined by the formula σ = n × μ × q (n: carrier concentration, μ: ion mobility, q: charge). The lithium salt concentration directly affects n and μ, and the two compete with each other. In preparing the third slurry, by controlling the mass fraction of the third lithium salt to 1%-10%, more Li... + The polymer chain segments are effectively dissociated by the third PVDF (especially the highly polar β phase), increasing the carrier concentration n. Simultaneously, the polymer chain segments react with Li... + The interaction between the polymer and ions enhances the mobility of Li, the ion mobility μ does not decrease significantly, and the conductivity reaches its peak. Furthermore, the concentration of the third lithium salt can affect the Li-ion interaction by altering the polymer-ion interaction. + The relative migration rates of the polymer and anions. Therefore, for PVDF-based systems, optimizing the concentration of the third lithium salt helps to utilize the polymer with specific anions (such as TFSI). - The interaction between the two restricts the movement of anions, thereby relatively increasing the lithium-ion transference number and thus optimizing the interface dynamics.

[0119] More importantly, in certain cases, the anions of specific lithium salts may interact with PVDF chains to promote the formation of a polar β phase, synergistically with the formation of a target β phase induced by stretching or polarization.

[0120] For example, the mass fraction of the third lithium salt in the third slurry can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any combination thereof.

[0121] In some embodiments, the third lithium salt may be at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0122] In some specific implementations, the stretching ratio of the polarized PVDF film precursor is (1.1-1.5):1.

[0123] When the precursor of a polarized PVDF film is stretched, the c-axis (molecular chain direction) and the direction of its strong dipole moment of the β-phase crystal will be highly preferentially oriented along the stretching direction. By controlling the stretching ratio, all dipole moment directions of the resulting β-phase crystal are made consistent, which is beneficial to enhancing the overall effective polarity of the polarized PVDF film in the thickness direction, thereby improving the dielectric properties and interfacial ion control capability of the polarized PVDF film as a polarization layer.

[0124] In addition, moderate stretching will cause the molecular chains to align and crystallize along the stretching direction, producing a "self-reinforcing" effect, which greatly improves the tensile strength and elastic modulus of the polarized PVDF film in this direction, and thus transforms into stronger mechanical barrier capability, which can more effectively resist the puncture of lithium dendrites.

[0125] For example, the stretch ratio of the polarized PVDF film precursor can be a range of 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, or any combination thereof.

[0126] In some specific implementations, the stretching rate is 1 mm / min to 5 mm / min.

[0127] By controlling the stretching rate to 1 mm / min–5 mm / min, the PVDF molecular chains are given sufficient time to relax, slip, and rearrange under external force, which theoretically facilitates the gradual and complete transformation of the α-phase crystal into the β-phase. Simultaneously, the stress has sufficient time to propagate and relax within the polarized PVDF film, promoting uniform deformation development. This helps obtain a polarized PVDF film with uniform thickness, dense structure, and no macroscopic defects, ensuring uniform current density within the battery and avoiding localized hot spots or preferential dendrite growth.

[0128] For example, the stretching rate can be a range of 1 mm / min, 2 mm / min, 3 mm / min, 4 mm / min, 5 mm / min, or any combination thereof.

[0129] In some specific embodiments, when preparing the first PVDF film, the first PVDF, the first solid electrolyte, and the first lithium salt are dispersed in a first solvent (such as NMP) to obtain a first slurry. The first slurry is then magnetically stirred overnight at 60°C. The first slurry stirred overnight is then transferred into a syringe and subjected to a first electrospinning method to form the first PVDF film by spinning on one side surface of the polarized PVDF film.

[0130] In some embodiments, the solid content of the first slurry is 10%-30%.

[0131] It is understandable that the solid content directly determines the viscosity, surface tension, and conductivity of the first slurry, which collectively affect the formation of the "Taylor cone" and the stability of the jet. Therefore, by controlling the solid content of the first slurry to 10%-30%, the optimal viscoelastic balance can be obtained. Under the action of an electric field, the droplets can form stable Taylor cones and be continuously stretched, refined, and solidified to form continuous, uniform nano / micron fibers with a narrow diameter distribution. The uniform and continuous fibers can form strong bonding points through physical entanglement or subsequent hot pressing, giving the first PVDF film good tensile strength, tear resistance, and flexibility. Optimizing the pore structure, mechanical strength, and flexibility of the resulting fiber membrane, and with an appropriate solid content, helps to uniformly suspend and encapsulate the first sulfide in the polymer solution. After spinning, the first sulfide particles are firmly embedded or encapsulated inside or on the surface of the fiber, forming continuous composite fibers, ensuring the effective construction of the sulfide ion conductive network.

[0132] For example, the solid content of the first slurry can be a range of 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or any combination thereof.

[0133] Similar to the above mechanism, the solid content of the second slurry can also be controlled between 10% and 30%.

[0134] For example, the solid content of the second slurry can be a range of 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, or any combination thereof.

[0135] It should be noted that the solid content of the first slurry and the second slurry may be the same or different.

[0136] In some specific embodiments, the mass fraction of the first PVDF in the first slurry is 20wt% to 30wt%.

[0137] By controlling the mass fraction of the first PVDF in the first slurry to be 20wt%-30wt%, a continuous and dense polymer network is formed in the resulting first PVDF film, providing sufficient mechanical support to suppress lithium dendrites while maintaining good flexibility to accommodate volume changes during battery assembly and cycling. This also ensures a good and tight solid-solid contact between the first PVDF film and the electrode, reducing interfacial impedance.

[0138] For example, the mass fraction of the first PVDF in the first slurry can be a range of 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, or any combination thereof.

[0139] Similar to the above mechanism, in some specific embodiments, the mass fraction of the second PVDF in the second slurry can also be 20wt%~30wt%.

[0140] For example, the mass fraction of the second PVDF in the second slurry can be a range of 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, or any combination thereof.

[0141] It should be noted that the mass fraction of the first PVDF in the first slurry and the mass fraction of the second PVDF in the second slurry may be the same or different.

[0142] In some specific embodiments, the mass fraction of the first solid electrolyte in the first slurry is 2wt% to 5wt%.

[0143] In some specific embodiments, the mass fraction of the second solid electrolyte in the second slurry may also be 2wt% to 5wt%.

[0144] For example, the mass fraction of the first solid electrolyte in the first slurry can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, or any combination thereof; the mass fraction of the second solid electrolyte in the second slurry can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, or any combination thereof.

[0145] It should be noted that the mass fraction of the second solid electrolyte may be the same as or different from that of the first solid electrolyte.

[0146] In some specific embodiments, the mass fraction of the first lithium salt in the first slurry is 1 wt% to 10 wt%.

[0147] In some specific embodiments, the mass fraction of the second lithium salt in the second slurry is 1wt% to 10wt%.

[0148] For example, the mass fraction of the first lithium salt in the first slurry is in the range of 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, or any two of these; and the mass fraction of the second lithium salt in the second slurry is in the range of 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, or any two of these.

[0149] It should be noted that the mass fractions of the first lithium salt and the second lithium salt may be the same or different.

[0150] In some specific embodiments, in the first electrospinning method, the supply rate of the first slurry is 0.5 ml / h-5 ml / h.

[0151] For example, the supply rate of the first slurry can be a range of 0.5 ml / h, 1 ml / h, 2 ml / h, 3 ml / h, 4 ml / h, 5 ml / h, or any combination thereof.

[0152] In some specific embodiments, in the first electrospinning method, the polarized PVDF film layer is attached to the first roller, and the rotational speed of the first roller is 100 rpm to 1500 rpm.

[0153] For example, the rotational speed of the first roller can be a range of 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, or any combination thereof.

[0154] In some specific implementations, the spinning distance of the first electrospinning method is 10cm-20cm.

[0155] For example, the spinning distance of the first electrospinning method can be a range of 10cm, 12cm, 14cm, 16cm, 18cm, 20cm or any combination thereof.

[0156] In some specific implementations, the spinning distance of the first electrospinning can be 10cm-30cm.

[0157] For example, the spinning distance can be a range of 10cm, 12cm, 14cm, 16cm, 18cm, 20cm, 22cm, 24cm, 26cm, 28cm, 30cm or any combination thereof.

[0158] It should be noted that the spinning distance should theoretically be equal to the slide distance.

[0159] In some specific implementations, the spinning pressure of the first electrospinning method is 10kV-20kV.

[0160] For example, the spinning pressure of the first electrospinning method can be a range of 10kV, 12kV, 14kV, 16kV, 18kV, 20kV or any combination thereof.

[0161] In some specific embodiments, the spinning temperature of the first electrospinning method is 25℃-40℃.

[0162] For example, the spinning temperature of the first electrospinning method can be a range of 25°C, 30°C, 35°C, 40°C, or any combination thereof.

[0163] In some specific embodiments, in the second electrospinning method, the supply rate of the second slurry is 0.5 ml / h-5 ml / h.

[0164] For example, the supply rate of the second slurry can be a range of 0.5 ml / h, 1 ml / h, 2 ml / h, 3 ml / h, 4 ml / h, 5 ml / h, or any combination thereof.

[0165] In some specific embodiments, in the second electrospinning method, a solid electrolyte bilayer film is attached to a second roller, and the rotational speed of the second roller is 100 rpm to 1500 rpm.

[0166] For example, the rotational speed of the solid electrolyte bilayer film can be a range of 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, or any combination thereof.

[0167] In some specific implementations, the spinning distance of the second electrospinning method is 10cm-20cm.

[0168] For example, the spinning distance of the second electrospinning method can be a range of 10cm, 12cm, 14cm, 16cm, 18cm, 20cm or any combination thereof.

[0169] In some specific implementations, the spinning distance of the second electrospinning can be 10cm-30cm.

[0170] For example, the spinning distance can be a range of 10cm, 12cm, 14cm, 16cm, 18cm, 20cm, 22cm, 24cm, 26cm, 28cm, 30cm or any combination thereof.

[0171] It should be noted that the spinning distance should theoretically be equal to the slide distance.

[0172] In some specific implementations, the spinning pressure of the second electrospinning method is 10kV-20kV.

[0173] For example, the spinning pressure of the second electrospinning method can be a range of 10kV, 12kV, 14kV, 16kV, 18kV, 20kV or any combination thereof.

[0174] In some specific embodiments, the spinning temperature of the second electrospinning method is 25℃-40℃.

[0175] For example, the spinning temperature of the second electrospinning method can be a range of 25°C, 30°C, 35°C, 40°C, or any combination thereof.

[0176] It should be noted that the process conditions for the first electrospinning method and the second electrospinning method may be the same or different.

[0177] In some specific embodiments, the temperature for heat treatment of the obtained solid electrolyte composite film precursor is 110℃-150℃, and the heat treatment time is 0.5min-5min.

[0178] Before heat treatment, the first, polarized, and third PVDF layers are primarily in physical contact. After heat treatment, the PVDF molecular chains on the surface of each layer gain mobility, diffuse and entangle with each other, transforming the clear physical interfaces into blurred, interpenetrating chemical / physical interfaces. The tiny air gaps or pores between layers are filled after polymer softening, forming a dense, defect-free integrated structure. This significantly reduces interlayer impedance, ensuring smooth and unimpeded lithium-ion transport between the three layers; simultaneously, it eliminates mechanical failure points caused by interlayer delamination, resulting in a substantial improvement in overall mechanical strength. Furthermore, appropriate heat treatment helps release residual stress introduced by the previous stretching process, stabilizes the formed β phase, and prevents it from transforming into other crystalline phases during use.

[0179] For example, the temperature of the heat treatment can be a range of 110°C, 120°C, 130°C, 140°C, 150°C or any combination thereof; the time of the heat treatment can be a range of 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min or any combination thereof.

[0180] The solid electrolyte composite film preparation method provided in this application optimizes the β-phase PVDF content in the polarized PVDF film by stretching, and forms a first PVDF film and a second PVDF film on both sides of the polarized PVDF film by electrospinning. Finally, the three PVDF film layers are cured by heat treatment to achieve the preparation of a solid electrolyte composite film with high β-phase PVDF content.

[0181] This application also provides an all-solid-state battery, including a positive electrode, a negative electrode, and the above-mentioned solid electrolyte composite film.

[0182] In some specific embodiments, the all-solid-state battery can be prepared according to conventional methods in the art. Specifically, it can be prepared according to the following steps:

[0183] Preparation of positive electrode sheet: The positive electrode active material, conductive agent, and binder (such as PVDF) are homogenized in NMP at a mass ratio of 8:1:1 and coated onto aluminum foil. After drying, the mixture is pressed into sheets, punched into small round sheets (such as 12 mm in diameter), vacuum dried at 120°C for 12 hours, and then transferred to a glove box. Preparation of lithium metal negative electrode sheet: Lithium sheets (14-15 mm in diameter) are cut in a glove box, and the surface oxide layer is scraped off.

[0184] Battery assembly: Take the negative electrode shell (CR2032 lower shell) as the bottom of the battery; place the lithium metal negative electrode sheet; place the solid electrolyte composite film (16mm in diameter, ensuring complete coverage of the negative electrode); place the positive electrode sheet (12mm in diameter, centered); place the gasket and spring sheet in sequence; cover with the positive electrode shell (upper shell); seal with a button cell battery sealing machine under appropriate pressure (usually 0.5-1 ton) to ensure tight contact between all internal layers.

[0185] The all-solid-state battery provided in this embodiment can perform the methods provided in the above-described method embodiments, and its implementation principle and technical effect are similar, so it will not be described in detail here.

[0186] This application also provides a battery pack comprising at least two of the aforementioned all-solid-state batteries.

[0187] The technical solution of this application will be further described below using specific embodiments.

[0188] Example 1

[0189] A solid electrolyte composite film includes a polarized PVDF film layer and a first PVDF film layer and a second PVDF film layer respectively disposed on both sides of the polarized PVDF film layer.

[0190] Its preparation method is as follows:

[0191] Weigh 10g of PVDF powder and 0.4g of lithium hexafluorophosphate (LiPF6), dissolve them in 30g of NMP, heat in a water bath to 60℃, and stir magnetically overnight to obtain a transparent solution with a PVDF mass fraction of 25wt%. Cast the transparent solution using a solution casting method and dry it at 70℃ to obtain a PVDF film. Then stretch the PVDF film at a stretching rate of 4mm / s with a stretching ratio of 1.5:1 to obtain a polarized PVDF film layer.

[0192] Weigh 10g of PVDF powder, 0.4g of lithium hexafluorophosphate (LiPF6), and 2g of LGPS, disperse them in 30g of xylene, and then heat in a water bath to 60℃ and stir magnetically overnight to obtain a first slurry with a solid content of 25%. Load the prepared first slurry into a syringe, attach a 20g (1 / 2-inch, flat-mouth) stainless steel needle to the syringe pump of an electrospinning machine, and connect the needle to the positive terminal of a high-voltage power supply. Then, install a first roller on the electrospinning machine, connect the first roller to the negative terminal of a high-voltage power supply, and attach a polarized PVDF film layer to the first roller. Control the liquid supply rate at 2.5ml / h, the first roller speed at 1000 rpm, the slide travel at 20cm, the spinning distance at 15cm, the spinning voltage at 15kV, the temperature at 35℃, and the humidity at 45% to obtain a solid electrolyte bilayer film comprising a first PVDF film layer and a polarized PVDF film layer.

[0193] Weigh 10g of PVDF powder, 0.4g of lithium hexafluorophosphate (LiPF6), and 2g of LGPS, disperse them in 30g of xylene, and then heat in a water bath to 60℃ and stir magnetically overnight to obtain a second slurry with a solid content of 25%. Load the prepared second slurry into a syringe, attach a 20g (1 / 2-inch, flat-tipped) stainless steel needle to the injection pump of the electrospinning machine, and connect the needle to the positive terminal of a high-voltage power supply. Then, install a second roller on the electrospinning machine, connecting it to the negative terminal of the high-voltage power supply, and attach a solid electrolyte double-layer film to the second roller. Control the liquid supply rate at 2.5ml / h, the first roller speed at 1000 rpm, the slide stroke at 20cm, the spinning distance at 15cm, the spinning voltage at 15kV, the temperature at 35℃, and the humidity at 45%. A solid electrolyte composite film comprising a first PVDF film layer, a second PVDF film layer, and a polarized PVDF film layer is obtained.

[0194] Example 2

[0195] A solid electrolyte composite membrane has a structure that is basically the same as that of Example 1, except that the first solid electrolyte used in the first PVDF membrane layer and the second solid electrolyte used in the second PVDF membrane layer are both LPSCI.

[0196] The preparation method is basically the same as that in Example 1, except that the stretching rate of the PVDF film is 5 mm / s when preparing the polarized PVDF film; and LGPS is replaced with LPSCI when preparing the first PVDF film and the second PVDF film.

[0197] Example 3

[0198] A solid electrolyte composite membrane has a structure that is basically the same as that in Example 1, except that the first solid electrolyte used in the first PVDF membrane layer is LATP, and the second solid electrolyte used in the second PVDF membrane layer is LLNOF.

[0199] The preparation method is basically the same as that in Example 1, except that the stretching rate of the PVDF film is 3 mm / s when preparing the polarized PVDF film; at the same time, when preparing the first PVDF film, the first solid electrolyte LGPS is replaced with LATP, and when preparing the second PVDF film, LGPS is replaced with LLNOF.

[0200] Example 4

[0201] A solid electrolyte composite membrane, the structure of which is basically the same as that in Example 1.

[0202] The preparation method is basically the same as that in Example 1, except that the stretching rate of the PVDF film is 1 mm / s when preparing the polarized PVDF film.

[0203] Example 5

[0204] A solid electrolyte composite membrane has a structure that is basically the same as that in Example 1, except that the first solid electrolyte used in the first PVDF membrane layer is LPSCI, and the second solid electrolyte used in the second PVDF membrane layer is LLNOF.

[0205] The preparation method is basically the same as that in Example 1, except that the rotation speed of the first roller is 500 rpm; at the same time, when preparing the first PVDF membrane layer, the first solid electrolyte LGPS is replaced with LPSCI, and when preparing the second PVDF membrane layer, LGPS is replaced with LLNOF.

[0206] Example 6

[0207] A solid electrolyte composite membrane, the structure of which is basically the same as that of Example 5.

[0208] The preparation method is basically the same as that in Example 5, except that the rotation speed of the first roller is 100 rpm.

[0209] Example 7

[0210] A solid electrolyte composite membrane, the structure of which is basically the same as that in Example 1.

[0211] The preparation method is basically the same as that in Example 1, except that the rotation speed of the first roller is 1500 rpm.

[0212] Example 8

[0213] A solid electrolyte composite membrane has a structure that is basically the same as that of Example 5, except that the first solid electrolyte used in the first PVDF membrane layer is LLNOF, and the second solid electrolyte used in the second PVDF membrane layer is LPSCI.

[0214] The preparation method is basically the same as that in Example 5, except that the rotation speed of the second roller is 1500 rpm; at the same time, when preparing the first PVDF membrane layer, the first solid electrolyte LPSCI is replaced with LLNOF, and when preparing the second PVDF membrane layer, the second solid electrolyte LLNOF is replaced with LPSCI.

[0215] Example 9

[0216] A solid electrolyte composite membrane has a structure that is basically the same as that of Example 1, except that in the first PVDF membrane layer, the mass ratio of the first PVDF to the first solid electrolyte LGPS is 1:0.1, and in the second PVDF membrane layer, the mass ratio of the second PVDF to the second solid electrolyte LGPS is 1:0.1.

[0217] The preparation method is basically the same as that in Example 1, except that the mass of the first solid electrolyte LGPS used in preparing the first PVDF membrane is 1g, and the mass of the second solid electrolyte LGPS used in preparing the second PVDF membrane is 1g.

[0218] Example 10

[0219] A solid electrolyte composite membrane has a structure that is basically the same as that in Example 1, except that in the first PVDF membrane layer, the mass ratio of the first PVDF to the first solid electrolyte LGPS is 1:1, and in the second PVDF membrane layer, the mass ratio of the second PVDF to the second solid electrolyte LGPS is 1:0.6.

[0220] The preparation method is basically the same as that in Example 1, except that the mass of the first solid electrolyte LGPS used in preparing the first PVDF membrane is 10g, and the mass of the second solid electrolyte LGPS used in preparing the second PVDF membrane is 6g.

[0221] Comparative Example 1

[0222] A solid electrolyte composite film has a structure that is basically the same as that of Example 1, except that it does not include a first PVDF film layer, but only contains a polarized PVDF film layer and a second PVDF film layer; its preparation method is also basically the same as that of Example 1, except that the first PVDF film layer is not prepared.

[0223] Comparative Example 2

[0224] A solid electrolyte composite film has a structure that is basically the same as that of Example 1, except that it does not include a second PVDF film layer, but only contains a polarized PVDF film layer and a first PVDF film layer; its preparation method is also basically the same as that of Example 1, except that the second PVDF film layer is not prepared.

[0225] Comparative Example 3

[0226] A solid electrolyte composite film has a structure that is basically the same as that of Example 1, except that it does not include either a first PVDF film layer or a second PVDF film layer, but only contains a polarized PVDF film layer; its preparation method is also basically the same as that of Example 1, except that neither the first PVDF film layer nor the second PVDF film layer is prepared.

[0227] The films prepared in the above examples and comparative examples were subjected to the following performance tests:

[0228] Thickness: Place the solid electrolyte composite film flat between the measuring anvils of the Mitutoyo MDC-25MX micrometer, gently rotate the micrometer screw until it contacts, and read the value; measurements must be taken at different locations on the film (at least 5 points, such as the center and four corners) and the average value must be taken to evaluate uniformity.

[0229] Ionic conductivity: In a glove box, a die-cut solid electrolyte composite film disc is sandwiched between two highly polished, clean stainless steel sheets; it is then placed in a coin cell casing and sealed under constant pressure using a sealing machine; the EIS spectrum of the coin cell is obtained using an electrochemical workstation, and the intercept of the high-frequency end of the spectrum with the real axis (Z' axis) is found; this value is the bulk resistance R. b The ionic conductivity is calculated using the following formula:

[0230]

[0231] Where σ: ionic conductivity; L: average thickness of the solid electrolyte composite film; R b A: Bulk resistance; B: Effective contact area between the stainless steel electrode and the solid electrolyte composite film.

[0232] PVDF film crystallinity:

[0233] The thermal properties of PVDF film samples were tested using differential scanning calorimetry (DSC). Under nitrogen protection, the samples were heated at a set heating rate to obtain the integral enthalpy of the melting peak. The crystallinity of the film material was then calculated using the standard enthalpy of melting of theoretically fully crystallized PVDF. The calculation formula is as follows:

[0234]

[0235] Where Xc is the crystallinity of the PVDF film, and ΔH m The enthalpy of melting of the sample is ΔH. m 0 The theoretical melting enthalpy is 100% crystalline PVDF, and m is the PVDF mass fraction. Crystallinity is used to characterize the degree of regularity of polymer chain segments and the proportion of crystalline regions, which can further reflect the mechanical stability and ion transport performance of the membrane material.

[0236] The proportion and mass percentage of β phase in each layer:

[0237] Quantitative analysis of the β-crystalline phase in each film layer was performed using Fourier transform infrared spectroscopy (FTIR), among which, 763 cm⁻¹ -1 The absorption peak at 840 cm⁻¹ is a characteristic peak of the α phase. -1 The absorption peak at 840 cm⁻¹ is a characteristic peak of the β phase. The relative content of the β phase is calculated by measuring the absorption intensities of the characteristic peaks of the β and α phases and applying the Lambert-Beer law. The calculation formula is as follows: F(β) = A(β) / (1.26A(α) + A(β)); where F(β) is the relative content of the β phase, and A(β) is the value at 840 cm⁻¹. -1 The characteristic peak absorption intensity is A(α) at ​​763 cm⁻¹. -1 The characteristic peak absorption intensity is shown. The β phase belongs to the all-trans (TTTT) chain conformation, which has a high dipole moment and polarization ability. The higher its mass percentage, the more beneficial it is to lithium salt dissociation, ion transport and interface stability. Therefore, the β phase content is usually used as an important evaluation index for high-performance PVDF-based electrolyte membranes. β phase mass percentage = F(β) * Xc.

[0238] PVDF membrane α phase ratio and mass percentage:

[0239] The proportion of the α phase can be calculated from the proportion of the β phase: F(α) = 1 - F(β), and the mass percentage of the α phase = F(α) * Xc.

[0240] The test results are detailed in Table 1.

[0241] Table 1

[0242]

[0243] As shown in Table 1, the solid electrolyte composite film provided in this application has a density of not less than 2.25 × 10⁻⁶. - 4 S·cm -1 ionic conductivity.

[0244] Compared with Comparative Examples 1-3, Example 1 has a higher ionic conductivity. It can be seen that in the solid electrolyte composite film provided in this application, the first PVDF film layer, the polarized PVDF film layer, and the second PVDF film layer are all indispensable for obtaining a high ionic conductivity.

[0245] The thin films obtained in the above embodiments and comparative examples were assembled into all-solid-state batteries according to the following steps:

[0246] Preparation of positive electrode sheet: The positive electrode active material, conductive agent, and binder (such as PVDF) are homogenized in NMP at a mass ratio of 90:5:5 and coated onto aluminum foil. After drying, the sheet is pressed and cut into small round sheets (such as 12 mm in diameter). The sheets are vacuum dried at 120°C for 12 hours and then transferred to a glove box.

[0247] Preparation of lithium metal anode sheet: Cut lithium sheet (14-15 mm in diameter) in a glove box and scrape off the surface oxide layer;

[0248] Battery assembly: Take the negative electrode shell (CR2032 lower shell) as the bottom of the battery; place the lithium metal negative electrode sheet; place the solid electrolyte composite film (16mm in diameter, ensuring complete coverage of the negative electrode); place the positive electrode sheet (12mm in diameter, centered); place the gasket and spring sheet in sequence; cover with the positive electrode shell (upper shell); seal with a button cell battery sealing machine under appropriate pressure (usually 0.5-1 ton) to ensure tight contact between all internal layers.

[0249] The prepared all-solid-state battery was subjected to the following performance tests:

[0250] Coulombic efficiency (characterizing rate performance): Tested using an electrochemical workstation. First, charge at a constant current of 0.5C to the cutoff voltage of 4.3V, then charge at a constant voltage until the current decays to 0.05C, and then discharge at a constant current of 0.2C to 2.8V. Calculate the discharge capacity / charge capacity × 100%, which is the coulombic efficiency of the all-solid-state battery.

[0251] Capacity retention (characterizing cycle stability): After 100 cycles according to the rate performance test procedure, calculate the discharge capacity of the 100th cycle / the discharge capacity of the first cycle × 100%, which is the capacity retention of the all-solid-state battery after 100 cycles.

[0252] The test results are detailed in Table 2:

[0253] Table 2

[0254]

[0255] As shown in Table 2, the solid electrolyte composite film provided in this application is used to prepare solid-state batteries. The resulting batteries have a coulombic efficiency greater than or equal to 90.1% and a capacity retention rate greater than or equal to 87.5% after 100 cycles, exhibiting excellent electrochemical performance.

[0256] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A solid electrolyte composite film, characterized in that, It includes a polarized PVDF film layer and a first PVDF film layer and a second PVDF film layer respectively disposed on both sides of the polarized PVDF film layer; The polarized PVDF film includes a first crystalline phase, which includes a first β-phase PVDF.

2. The solid electrolyte composite film according to claim 1, characterized in that, The mass percentage of the first β-phase PVDF in the first crystalline phase is 30%-90%.

3. The solid electrolyte composite film according to claim 1 or 2, characterized in that, The first PVDF film layer includes a first PVDF, a first solid electrolyte, and a first lithium salt; And / or, the second PVDF membrane layer includes a second PVDF, a second solid electrolyte, and a second lithium salt.

4. The solid electrolyte composite film according to claim 3, characterized in that, In the first PVDF membrane layer, the mass ratio of the first PVDF to the first solid electrolyte is 1:(0.1-1). And / or, in the second PVDF film layer, the mass ratio of the second PVDF to the second solid electrolyte is 1:(0.1-0.6). And / or, the mass fraction of the first lithium salt in the first PVDF film is 1%-10%; And / or, the mass fraction of the second lithium salt in the second PVDF film is 1%-10%.

5. The solid electrolyte composite film according to claim 3, characterized in that, The first solid electrolyte includes one of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium sulfur phosphorus chlorine, lithium sulfur phosphorus germanium, lithium lanthanum niobium oxyfluorine, polyethylene glycol dimethacrylate, and polyethylene terephthalate acrylate. And / or, the second solid electrolyte comprises one of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium sulfur phosphorus chloride, lithium sulfur phosphorus germanium, lithium lanthanum niobium oxyfluorine, polyethylene glycol dimethacrylate, and polyethylene terephthalate acrylate. And / or, the first lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethanesulfonyl)imide; And / or, the second lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.

6. The solid electrolyte composite film according to claim 1, characterized in that, The first PVDF film layer includes a second crystalline phase, and the second crystalline phase includes a second β-phase PVDF; The mass percentage of the second β-phase PVDF in the second crystalline phase is 24%-88%; And / or, the second PVDF film layer includes a third crystalline phase, the third crystalline phase including a third β-phase PVDF; The mass percentage of the third β-phase PVDF in the third crystalline phase is 24%-88%.

7. The solid electrolyte composite film according to claim 1, characterized in that, The thickness of the solid electrolyte composite film is 10µm to 20µm.

8. A method for preparing a solid electrolyte composite thin film according to any one of claims 1-7, characterized in that, include: A third slurry containing a third PVDF and a third lithium salt is used to prepare a third PVDF film layer, and then the third PVDF film layer is stretched to obtain a polarized PVDF film layer. A first PVDF, a first solid electrolyte, and a first lithium salt are dissolved in a first solvent to form a first slurry. The first slurry is then used to form a first PVDF film layer on one side surface of the polarized PVDF film layer by a first electrospinning method, thereby obtaining a solid electrolyte bilayer film. The second PVDF, the second solid electrolyte, and the second lithium salt are dissolved in a second solvent to form a second slurry; the second slurry is then used to form a second PVDF film layer on the other surface of the solid electrolyte bilayer film by a second electrospinning method, thus obtaining a solid electrolyte composite film precursor. The solid electrolyte composite film precursor is heat-treated to obtain the solid electrolyte composite film.

9. The method for preparing a solid electrolyte composite thin film according to claim 8, characterized in that, The mass fraction of the third PVDF in the third slurry is 5%~27.5%; And / or, the third lithium salt has a mass fraction of 1%-10% in the third slurry; And / or, the stretching ratio is (1.1-1.5):1; And / or, the stretching rate is 1 mm / min to 5 mm / min.

10. The method for preparing a solid electrolyte composite film according to claim 8, characterized in that, The solid content of the first slurry is 10%-30%; And / or, the mass fraction of the first PVDF in the first slurry is 20wt%~30wt%; And / or, the mass fraction of the first solid electrolyte in the first slurry is 2wt%~5wt%; And / or, the mass fraction of the first lithium salt in the first slurry is 1 wt% to 10 wt%; And / or, the solid content of the second slurry is 20%-30%; And / or, the mass fraction of the second PVDF in the second slurry is 20wt%~30wt%; And / or, the mass fraction of the second solid electrolyte in the second slurry is 2wt%~5wt%; And / or, the mass fraction of the second lithium salt in the second slurry is 1wt% to 10wt%.

11. The method for preparing a solid electrolyte composite thin film according to claim 8, characterized in that, In the first electrospinning method, the supply rate of the first slurry is 0.5 ml / h-5 ml / h; And / or, in the first electrospinning method, the polarized PVDF film layer is attached to the first roller, and the rotational speed of the first roller is 100 rpm to 1500 rpm; And / or, the spinning distance of the first electrospinning method is 10cm-20cm; And / or, the spinning pressure of the first electrospinning method is 10kV-20kV; And / or, the spinning temperature of the first electrospinning method is 25℃-40℃.

12. The method for preparing a solid electrolyte composite film according to claim 8, characterized in that, In the second electrospinning method, the supply rate of the second slurry is 0.5 ml / h-5 ml / h; And / or, in the second electrospinning method, the solid electrolyte bilayer film is attached to a second roller, the second roller rotating at a speed of 100 rpm to 1500 rpm; And / or, the spinning distance of the second electrospinning method is 10cm-20cm; And / or, the spinning pressure of the second electrospinning method is 10kV-20kV; And / or, the spinning temperature of the second electrospinning method is 25℃-40℃.

13. The method for preparing a solid electrolyte composite thin film according to claim 8, characterized in that, The heat treatment temperature is 110℃-150℃; The heat treatment time is 0.5 min to 5 min.

14. An all-solid-state battery, characterized in that, It includes a positive electrode, a negative electrode, and a solid electrolyte composite film as described in any one of claims 1-7 or a solid electrolyte composite film prepared by any one of claims 8-13.

15. A battery pack, characterized in that, Includes at least two of the all-solid-state batteries as described in claim 14.